RNA Misprocessing in C9orf72-Linked Neurodegeneration - Barker, Holly V.; Niblock, Michael; Lee, Youn-Bok; Shaw, Christopher E.; Gallo, Jean-Marc (Frontiers in Cellular Neuroscience, 2017)
A large GGGGCC hexanucleotide repeat expansion in the first intron or promoter region of the C9orf72 gene is the most common genetic cause of familial and sporadic Amyotrophic lateral sclerosis (ALS), a devastating degenerative disease of motor neurons, and of Frontotemporal Dementia (FTD), the second most common form of presenile dementia after Alzheimer’s disease. C9orf72-associated ALS/FTD is a multifaceted disease both in terms of its clinical presentation and the misregulated cellular pathways contributing to disease progression. Among the numerous pathways misregulated in C9orf72-associated ALS/FTD, altered RNA processing has consistently appeared at the forefront of C9orf72 research. This includes bidirectional transcription of the repeat sequence, accumulation of repeat RNA into nuclear foci sequestering specific RNA-binding proteins, and translation of RNA repeats into dipeptide repeat proteins by repeat-associated non-AUG-initiated translation. Over the past few years the true extent of RNA misprocessing in C9orf72-associated ALS/FTD has begun to emerge and disruptions have been identified in almost all aspects of the life of an RNA molecule, including release from RNA polymerase II, translation in the cytoplasm and degradation. Furthermore, several alterations have been identified in the processing of the C9orf72 RNA itself, in terms of its transcription, splicing, and localisation. This review aims to consolidate our current knowledge on the consequence of the C9orf72 repeat expansion on RNA processing and draws attention to the mechanisms by which several aspects of C9orf72 molecular pathology converge to perturb every stage of RNA metabolism.